Bibliometric Analysis on the Role of Government and Policy in Promoting Workplace Gender Equality - Luintel, Jyoti (NCC Journal, 2024)
Workplace gender equality remains a critical global challenge despite decades of legislative and policy interventions. This study employs a comprehensive bibliometric analysis to explore the evolving landscape of research on the role of government and policy in promoting gender equality in the workplace. Drawing on a dataset of 261 documents using Scopus publications from 1990 to 2024, the analysis reveals key trends, influential works, and thematic developments that have shaped the field. The findings underscore the central role of government policies, including public policy frameworks, socioeconomic considerations, and corporate  governance  reforms,  in  advancing  gender  parity.  Notably,  the  study identifies emerging areas of interest, such as the intersection of gender equality with environmental sustainability and  socioeconomic  factors  that  signals  new  directions  for  future  research. Despite significant progress, the persistence of gender disparities in various sectors highlights the need for continued scholarly and policy efforts. This study provides a robust foundation for understanding the impact of government interventions on workplace gender equality and offers critical insights for shaping future research and policy agendas.